2020
DOI: 10.3389/fpls.2019.01694
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Class I Trehalose Biosynthesis Genes in Physcomitrella patens

Abstract: The function of trehalose metabolism in plants during growth and development has been extensively studied, mostly in the eudicot Arabidopsis thaliana. So far, however, not much is known about trehalose metabolism in the moss Physcomitrella patens. Here, we show that in P. patens, two active trehalose-6-phosphate synthase enzymes exist, PpTPS1 and PpTPS2. Expression of both enzymes in Saccharomyces cerevisiae can complement the glucose-growth defect of the yeast tps1Δ mutant. Truncation of N-terminal extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Sugar sensing is not completely abolished in tps1∆ tps2∆ mutants, but these mutants are less responsive to glucose and sucrose treatment than wild type and indeed tps1∆ mutants. Collectively, these findings demonstrate that PpTPS1 and PpTPS2 are required for the perception of both sugars and hormones, but likely act with other factors such as Class II TPS enzymes or SNF1‐related kinases (SnRKs) (Phan et al, 2020). This is in line with reports of a link between Tre‐6P concentration and sugar availability, as well as Tre‐6P mediated inhibition of SnRK1 in Arabidopsis (Lunn et al, 2006; Y. Zhang et al, 2009).…”
Section: Sugarmentioning
confidence: 97%
See 3 more Smart Citations
“…Sugar sensing is not completely abolished in tps1∆ tps2∆ mutants, but these mutants are less responsive to glucose and sucrose treatment than wild type and indeed tps1∆ mutants. Collectively, these findings demonstrate that PpTPS1 and PpTPS2 are required for the perception of both sugars and hormones, but likely act with other factors such as Class II TPS enzymes or SNF1‐related kinases (SnRKs) (Phan et al, 2020). This is in line with reports of a link between Tre‐6P concentration and sugar availability, as well as Tre‐6P mediated inhibition of SnRK1 in Arabidopsis (Lunn et al, 2006; Y. Zhang et al, 2009).…”
Section: Sugarmentioning
confidence: 97%
“…Comparative analyses of Tre‐6P levels between these mutants suggest that PpTPS1 is likely to be more active than PpTPS2 , since the concentration of Tre‐6P is significantly lower in tps1∆ mutants than in tps2 ∆ mutants. Interestingly, low levels of Tre‐6P are detectable in tps1∆tps2∆ mutants, but this is likely due to a basal level of TPS activity exhibited by the Class II TPS proteins (Phan et al, 2020).…”
Section: Sugarmentioning
confidence: 99%
See 2 more Smart Citations
“…Trehalose is a non-reducing sugar composed of two glucose molecules with 1,1-glycosidic bonds [ 41 ], and can be used as a source of carbohydrates, in addition to a typical stress protectant to maintain cell homeostasis [ 42 ]. Previous research has shown that trehalose can improve the antifreeze performance of L. edodes and P. ostreatus , and the growth of mycelia on medium containing trehalose is better than that on medium containing glucose [ 43 ].…”
Section: Discussionmentioning
confidence: 99%